A Foreign Voyage Pacific Maritime Labour Identity, 1840-1890 - Grider, John T. (UJ Press, 2017)
JOHN GRIDER joined the Institute for Reconciliation and Social Justice at the University of the Free State as a Research Fellow in November 2015. He recently completed this captivating project, which investigates the complex interplay between gender, class and race sourced from the narratives of men who found themselves working in the transforming Pacific maritime industry during the mid-nineteenth century.